Rancang Bangun Otomatisasi Lampu Perangkap Hama Tenaga Surya Pada Tanaman Bawang Merah - Andy Suprayoga; Elsanda Merita Indrawati; Kartika Rahayu Tri Prasetyo Sari; Hisbulloh Ahlis Munawi (Universitas Islam Raden Rahmat, Malang, 2023)
The use of pesticides for handling pests on shallots causes a bad impact on the environment, as a result, the researchers designed the design of solar-powered pest lights on shallot plants that were effective in catching shallot pests and practical in use. The experiment was carried out twice in the onion plant area. As a result, on the first day of the experiment, the lamp was able to light up steadily at 05.30 p.m -05.30 a.m and was able to catch 8 ounces of pests and on the second day of the experiment the lamp was able to light up steadily at 05.30 p.m-04.15 a.m and was able to catch 5.2 ounces of pests.